Visiting ‘Peter in Chains’: French Pilgrimage to Rome, 1873–93 - Brennan, Brian (The journal of ecclesiastical history, 2000)
Inscribed on the wall of the expiatory Basilica of Sacré Coeur, at Montmartre, the 1873 ‘national vow’ of France interprets the nation's recent misfortunes as divine chastisement of an errant and irreligious people. Since it was Napoleon III's withdrawal of French troops from Rome that had made it possible for the Italian forces to capture the papal city in September 1870, the ‘national vow’ reflects a strong sense of French responsibility for the pope's loss of his temporal power. The Catholic Right interpreted France's defeat in the Franco-Prussian war, and her subsequent loss of Alsace and Lorraine, as God's punishment on ‘the eldest daughter of the Church’ for her desertion of the Vicar of Christ, and the ‘national vow’ pledged prayer for the Roman pontiff's deliverance from his enemies. This study analyses the devotion of French Catholics to ‘the prisoner of the Vatican’ during the Third Republic through an exploration of some of the religious and political meanings of pilgrimage to visit ‘Peter in chains’. It also charts the process by which promotion in the Catholic press, rapid train transportation and cheaper package fares opened an era of mass pilgrimage to Rome and paved the way for a new popular papal style.